"Your Diet is a Bank Account; Good Food Choices are Good Investment"; COVID-19 and Dieting - Asifa Siraj; Zainah Kashif; Uzma Urooj; Uzma Saleem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To gain insight into the relationship between dieting and unhealthy eating habits with COVID-19 infections and complications.